Social-demographic factors of providing regional economic security (by the data of Omsk oblast) - E. A. Kapoguzov; R. I. Chupin; M. S. Kharlamova; A. S. Tsaturyan (Russian Journal of Economics and Law)
Objective: to develop an approach to assess the regional economic security indicators by supplementing them with socio- demographic factors and actualization of socio-demographic threats to the level of a certain region by assessing the probabilities of implementing social development scenarios in the region.Methods: general scientific methods of cognition were used in the research process; demographic threats to economic security were identified on the basis of regression analysis of secondary information (Rosstat data); the probability of implementing social development scenarios was estimated using the expert-statistical Bayesian method based on the data of the expert survey conducted by the authors.Results: the issues of economic security are widely covered in the scientific literature of recent years. However, the assessment of economic security practically ignores the social and demographic factors of its provision, which, meanwhile, have a significant impact on the development of territories. The paper identifies the need to develop a system of indicators that take into account the impact of social and demographic factors on the economic security of a territory. Based on the regression analysis conducted in 77 regions of the Russian Federation, a significant relationship between demographic processes and social well-being of the region was established, which allowed identifying the demographic threats to economic security. For each threat, events were described, and a priori and a posteriori chances of events were calculated with an expert survey method by the example of the Omsk region. As a result of the study, we propose estimations of the probability of social development scenarios of the region, where the considered demographic problems have shown high relevance, since all scenarios have chances significantly different from zero, while the most likely is the movement in the direction of “society of universal risk” (35%).Scientific novelty: given the variety of approaches to the definition and assessment of economic security, only a limited list of techniques is institutionalized, which does not always contribute to the timely prevention of threats. The study proposes to supplement the system of regional economic security indicators with a list of social and demographic factors. Also, we propose a method of social and demographic threats actualization at the level of a certain region by assessing the probabilities of the social development scenarios implementation on the basis of an expert survey.Practical significance: the results obtained can be used as recommendations for regional authorities in the assessment and development of measures for the timely prevention of social and demographic threats to regional economic security.